2015
DOI: 10.1007/s10653-015-9676-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of fluoride concentrations in groundwater resources of Larestan and Gerash regions in Iran from 2003 to 2010

Abstract: There is discrepancy about intervals of fluoride monitoring in groundwater resources by Iranian authorities. Spatial and temporal variability of fluoride in groundwater resources of Larestan and Gerash regions in Iran were analyzed from 2003 to 2010 using a geospatial information system and the Mann-Kendall trend test. The mean concentrations of fluoride for the 8-year period in the eight cities and 31 villages were 1.6 and 2.0 mg/l, respectively; the maximum values were 2.4 and 3.8 mg/l, respectively. Spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Amouei found that the concentra- tion of fluoride in rural areas of Khaf was 0.11 to 3.59 mg/l. He reported that the fluoride concentration in 31% of the samples was less than the standard, 4% was above the standard and 64% were within standard range [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amouei found that the concentra- tion of fluoride in rural areas of Khaf was 0.11 to 3.59 mg/l. He reported that the fluoride concentration in 31% of the samples was less than the standard, 4% was above the standard and 64% were within standard range [22].…”
Section: Discussionmentioning
confidence: 99%
“…Amini assessed the mean concentrations of fluoride for the 8-y period in the study area were 1.6 and 2.0 mg/l, respectively and Spatial, temporal, and spatiotemporal variability of fluoride in overall groundwater resources were relatively constant over the years [22].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy one samples of different brands of bottled waters were chosen randomly, and then the fluoride concentration of water samples was determined by Ion Chromatography No. 4110 based on the method mentioned in the book of standard methods for water and wastewater experiments [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…In this study, 805 samples were analyzed by descriptive and analytical statistics (correlation coefficients) in 10 years ( Table 3 ). The important major cations and anions in water samples were analyzed following a standard method (APHA 2008) [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%